Karakteristik Ekstrak Saponin Pada Daun Kucai (Allium schoenoprasum) Asal Pontianak - Widiawati, Helen; Maherawati, Maherawati; Hartanti, Lucky (Universitas Tanjungpura, 2023)
Chives (allium schoenoprasum) is one of the tropical plants grown to harvest the leaves. Chives leaf extract has various health benefits because it contains several phytochemical compounds, namely flavonoids, tannins, triterpenoid, allicin and saponins. Saponin comes from the latin word